Moshi Monsters Pick your Path 3. - Holowaty, Lauren (London Ladybird Books Ltd., 2012)
Based on the awesome online world of Moshi Monsters, this book allows you to become your monster and explore Monstro City in this adventure.
Keywords: Children's stories